Major export destinations of Thailand: Evidence from copula-based simultaneous kink equation - Pathairat Pastpipatkul (2018)
© Published under licence by IOP Publishing Ltd. This paper assesses the nonlinear relationship between selected economic factors and Thailand's exports to its three major export partners namely the United States, Japan, and China by employing copula-based simultaneous kink equation (SKE) model. This is because there is an increase of empirical evidence of nonlinearities in regression models with macroeconomic time series. The practical result shows that there is a nonlinear relationship between the growth of Thai GDP and the growth of exports to Japan. The kink value in Thai GDP growth is 0.017, indicating that if Thai GDP growth is beyond 0.017%, the coefficient will be in the negative part which is 0.014. Thai exports to Japan will fall when Thai GDP growth moves across the kink point, which is a rather unexpected result. Overall, it refers that Thailand's GDP is the most crucial determinant of Thailand's exports since its significance obtains for Thailand's exports to both China and Japan.